Industrial exploitation of supercritical carbon dioxide as a solvent - Haddleton, Alice J. (2020)
The work described in this thesis can be divided into two main topic areas; the synthesis of polymer particles via dispersion polymerisation using supercritical carbon dioxide (scCO2) as the reaction medium and the scale-up of these reactions. The fundamental concepts used to achieve these aims are detailed in Chapter 1. As high pressures and temperatures are involved, utilising scCO2 as a reaction medium requires specialised equipment. The high-pressure equipment used throughout this thesis is summarised in Chapter 2. This includes the details of a 1 L high-pressure autoclave, previously only used for extraction, which has been used for the scale-up of polymer synthesis. The techniques used to analyse the polymers produced are also outlined. The first main topic area of this thesis is the synthesis of polymer particles via dispersion polymerisation, which is discussed in Chapter 3. The first structure investigated is a poly(methyl methacrylate) (PMMA) particle incorporating a crosslinking component. The loading of the crosslinking component was varied to establish the effect this had on the particle structure, as well as the glass transition temperature (Tg). These parameters were probed using scanning electron microscopy (SEM) and dynamic mechanical analysis (DMA) respectively. A second particle of interest contained a core-shell internal morphology. Two monomer composition were investigated, both containing a PMMA shell encasing either a poly(butyl acrylate) (PBA) or poly(benzyl acrylate) (PBzA) core. The loading of the core material (BA or BzA) was gradually increased and once again the changes in the particle morphology and Tg were probed. The ability to preferentially stain the PBzA allowed for probing of the internal morphology of the PBzA containing particles using transmission electron microscopy (TEM). Utilising scCO2 as the reaction medium removes the need for high-energy post polymerisation drying steps usually associated with dispersion polymerisations carried out in traditional solvents. However, despite numerous advantages, scale remains a hurdle which has thus far limited the applicability of scCO2 for the commercial production of polymer particles. As this thesis was industrially funded, the second topic area of investigation was the feasibility of increasing the scale of the high-pressure reactions, which is discussed in Chapter 4. The dispersion polymerisation of methyl methacrylate (MMA) was chosen as a model system as it has been well-studied in the literature. In this Chapter, comparisons are made between the particles produced on a small (60 mL) scale and those produced on a larger (1 L) scale using analogous reaction conditions. SEM was used to analyse the morphology of the particles produced. Control of the particle size, by variation of the concentration of the poly(dimethyl siloxane) stabiliser (PDMS) is demonstrated, with similar size particles being produced on both scales. The desired application for these particles is as impact modifiers. With this in mind, the synthesised particles were combined with various PVC formulations and tested at Kaneka Belgium. Several industrially standard tests were performed, including Brabender torque rheometry, transparency and Izod impact tests. The results of these tests are summarised in Chapter 5. Comparisons are made between the particles synthesised in Nottingham and those produced commercially by Kaneka, intended for the same application. These tests allowed for conclusions to be drawn about the composition of the particles as well as the internal morphology present. The data collected complimented the analysis carried out in Nottingham. It also provided an opportunity to assess areas that could be improved upon in the future production of particles.